Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.

Annual precipitation explains variability in dryland vegetation greenness globally but not locally - Anna M. Ukkola; Martin G. De Kauwe; Michael L. Roderick; Arden Burrell; Peter Lehmann; Andy J. Pitman (Global Change Biology, 2021)
Dryland vegetation productivity is strongly modulated by water availability. As precipitation patterns and variability are altered by climate change, there is a pressing need to better understand vegetation responses to precipitation variability in these ecologically fragile regions. Here we present a global analysis of dryland sensitivity to annual precipitation variations using long‐term records of normalized difference vegetation index (NDVI). We show that while precipitation explains 66% of spatial gradients in NDVI across dryland regions, precipitation only accounts for 75%) dryland regions. We observed this weaker temporal relative to spatial relationship between NDVI and precipitation across all global drylands. We confirmed this result using three alternative water availability metrics that account for water loss to evaporation, and growing season and precipitation timing. This suggests that predicting vegetation responses to future rainfall using space‐for‐time substitution will strongly overestimate precipitation control on interannual variability in aboveground growth. We explore multiple mechanisms to explain the discrepancy between spatial and temporal responses and find contributions from multiple factors including local‐scale vegetation characteristics, climate and soil properties. Earth system models (ESMs) from the latest Coupled Model Intercomparison Project overestimate the observed vegetation sensitivity to precipitation variability up to threefold, particularly during dry years. Given projections of increasing meteorological drought, ESMs are likely to overestimate the impacts of future drought on dryland vegetation with observations suggesting that dryland vegetation is more resistant to annual precipitation variations than ESMs project.

DNA Double-Strand Break Accumulation in Alzheimer’s Disease: Evidence from Experimental Models and Postmortem Human Brains - Nidheesh Thadathil; David F. Delotterie; Jianfeng Xiao; Roderick Hori; Michael P. McDonald; Mohammad Moshahid Khan (Molecular Neurobiology, 2021)

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

Phylogeography of the widespread creek chub Semotilus atromaculatus (Cypriniformes: Leuciscidae) - Susana Schönhuth; Roderick B. Gagne; Fernando Alda; David A. Neely; Richard L. Mayden; Michael J. Blum (Journal of Fish Biology, 2018)
The extent and nature of genetic differentiation in Semotilus atromaculatus , one of the most abundant and widespread leuciscids in North America, were evaluated based on mitochondrial (mt) and nuclear DNA sequence variation. Phylogenetic relationships were first inferred based on a fragment of the cytochrome b ( cytb ) region and the nuclear intron s7 gene for S. atromaculatus and all other congeners as well as representative species from all other genera in the creek chub–plagopterin clade. The phylogeography of major haplogroups of S. atromaculatus was also assessed according to variation in a fragment of the mitochondrial cytb region from 567 individuals across its range. All analyses identified S. thoreauianus , S. lumbee and S. corporalis as reciprocally monophyletic groups. Analyses of nuclear sequence variation resolved S. atromaculatus as a single clade, where S. thoreauianus and S. lumbee were recovered as the sister group to S. atromaculatus , and S. corporalis was resolved as sister to all other species in the genus. Analyses of mtDNA sequence variation recovered S. atromaculatus as three well supported and differentiated monophyletic groups, with a widespread genetically homogeneous lineage extending across most of the current range of the species; a more geographically restricted and geographically structured lineage in the southern Appalachians, sister group to S. lumbee ; and a geographically restricted lineage was identified from two Gulf Slope basins. Evidence of complex mito‐nuclear discordance and phylogeographic differentiation within S. atromaculatus illustrates that further analysis of widespread species is warranted to understand North American freshwater fish diversity and distributions.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Stream flow alone does not predict population structure of diving beetles across complex tropical landscapes - Athena Lam; Emmanuel F. A. Toussaint; Carolin Kindler; Matthew H. Van Dam; Rawati Panjaitan; George K. Roderick; Michael Balke (Molecular Ecology, 2018)
Recent theoretical advances have hypothesized a central role of habitat persistence on population genetic structure and resulting biodiversity patterns of freshwater organisms. Here, we address the hypothesis that lotic species, or lineages adapted to comparably geologically stable running water habitats (streams and their marginal habitats), have high levels of endemicity and phylogeographic structure due to the persistent nature of their habitat. We use a next RAD DNA sequencing approach to investigate the population structure and phylogeography of a putatively widespread New Guinean species of diving beetle, Philaccolilus ameliae (Dytiscidae). We find that P. ameliae is a complex of morphologically cryptic, but geographically and genetically well‐differentiated clades. The pattern of population connectivity is consistent with theoretical predictions associated with stable lotic habitats. However, in two clades, we find a more complex pattern of low population differentiation, revealing dispersal across rugged mountains and watersheds of New Guinea up to 430 km apart. These results, while surprising, were also consistent with the original formulation of the habitat template concept by Southwood, involving lineage‐idiosyncratic evolution in response to abiotic factors. In our system, low population differentiation might reflect a young species in a phase of range expansion utilizing vast available habitat. We suggest that predictions of life history variation resulting from the dichotomy between lotic and lentic organisms require more attention to habitat characterization and microhabitat choice. Our results also underpin the necessity to study fine‐scale processes but at a larger geographical scale, as compared to solely documenting macroecological patterns, to understand ecological drivers of regional biodiversity. Comprehensive sampling especially of tropical lineages in complex and threatened environments such as New Guinea remains a critical challenge.

Phylogeography and population genomics of a lotic water beetle across a complex tropical landscape - Athena Wai Lam; Morgan Gueuning; Carolin Kindler; Matthew Van Dam; Nadir Alvarez; Rawati Panjaitan; Helena Shaverdo; Lloyd T. White; George K. Roderick; Michael Balke (Molecular Ecology, 2018)
The habitat template concept applied to a freshwater system indicates that lotic species, or those which occupy permanent habitats along stream courses, are less dispersive than lentic species, or those that occur in more ephemeral aquatic habitats. Thus, populations of lotic species will be more structured than those of lentic species. Stream courses include both flowing water and small, stagnant microhabitats that can provide refuge when streams are low. Many species occur in these microhabitats but remain poorly studied. Here, we present population genetic data for one such species, the tropical diving beetle Exocelina manokwariensis (Dytiscidae), sampled from six localities along a ~300 km transect across the Birds Head Peninsula of New Guinea. Molecular data from both mitochondrial (CO1 sequences) and nuclear (ddRAD loci) regions document fine‐scale population structure across populations that are ~45 km apart. Our results are concordant with previous phylogenetic and macroecological studies that applied the habitat template concept to aquatic systems. This study also illustrates that these diverse but mostly overlooked microhabitats are promising study systems in freshwater ecology and evolutionary biology. With the advent of next‐generation sequencing, fine‐scale population genomic studies are feasible for small nonmodel organisms to help illuminate the effect of habitat stability on species’ natural history, population structure and geographic distribution.

Stepping‐stones across space and time: repeated radiation of Pacific flightless broad‐nosed weevils (Coleoptera: Curculionidae: Entiminae: Rhyncogonus ) - Elin M. Claridge; Rosemary G. Gillespie; Michael S. Brewer; George K. Roderick (Journal of Biogeography, 2017)
Aim We examine spatial and temporal patterns of diversification among flightless weevils in the genus Rhyncogonus (Curculionidae: Entiminae), with respect to their passive mode of dispersal by rafting or upon birds and the geological context of Pacific island archipelagos. Location Archipelagos and islands of the Pacific Ocean, especially the South Pacific and Hawaii. Methods Nuclear and mitochondrial DNA sequence data were used in Bayesian and maximum likelihood analyses to generate a phylogenetic hypothesis for all available species within the genus Rhyncogonus , plus representatives of other tribes in the subfamily Entiminae. Bayesian inference with molecular and geological calibration points was also used to estimate the age of major lineages of Rhyncogonus and infer the history of colonization. Results The genus Rhyncogonus has colonized all major archipelagos in the central Pacific, with multiple species occurring within nearly all archipelagos. The common ancestors of the genus were present in the central Pacific at least 15 Ma, probably first inhabiting islands now under water. Subsequent colonization and diversification across Oceania shows a pattern that is remarkably consistent with the geology of the region: the weevils, which likely disperse either by rafting on vegetation or on migratory birds, reached each island not long after its appearance. Main conclusions Though flightless, weevils in the genus Rhyncogonus have been remarkably effective at colonizing islands of the Pacific and appear to have colonized more remote islands via a series of less remote archipelagos. Although such a process of dispersal has been predicted, this study provides the first clear demonstration of the role of stepping‐stones in the diversification of a lineage with passive dispersal.

Farmers taking responsibility for herd health development—stable schools in research and advisory activities as a tool for dairy health and welfare planning in Europe - Silvia Ivemeyer; Nick J. Bell; Jan Brinkmann; Kornel Cimer; Elisabeth Gratzer; Christine Leeb; Solveig March; Cecilie Mejdell; Stephen Roderick; Gidi Smolders; Michael Walkenhorst; Christoph Winckler; et al. (Organic Agriculture, 2015)

Consensus Paper: Language and the Cerebellum: an Ongoing Enigma - Peter Mariën; Herman Ackermann; Michael Adamaszek; Caroline H. S. Barwood; Alan Beaton; John Desmond; Elke De Witte; Angela J. Fawcett; Ingo Hertrich; Michael Küper; Maria Leggio; Cherie Marvel; et al. (The Cerebellum, 2013)

Climate‐related trends in Australian vegetation cover as inferred from satellite observations, 1981–2006 - RANDALL J. DONOHUE; TIM R. McVICAR; MICHAEL L. RODERICK (Global Change Biology, 2009)
Using Advanced Very High Resolution Radiometer data spanning 1981–2006 and calibrated for long‐term analyses of vegetation dynamics, we examine whether vegetation cover has increased across Australia and whether there has been a differential response of vegetation functional types in response to changes in climatic growing conditions. Trends in vegetation cover are interpreted within Budyko's energy – water limitation framework. Results from an Australia‐wide analysis indicate that vegetation cover (as described by the fraction of Photosynthetically Active Radiation absorbed by vegetation; fPAR) has increased, on average, by 0.0007 per year – an increase of ∼8% over the 26 years. The majority of this change is due to a 0.0010 per year increase in persistent fPAR (representing nondeciduous perennial vegetation types; up 21%). In contrast, recurrent fPAR (representing deciduous, annual and ephemeral vegetation types) decreased, on average, by 0.0003 per year (down 7%), the trends of which are highly seasonal. Over the same period, Australian average annual precipitation increased by 1.3 mm yr −2 (up 7%). A site‐based analysis using 90 long‐term meteorological stations with minimal localized land‐cover changes showed that energy‐limited sites where total fPAR increased generally experienced decreases in precipitation, and water‐limited sites that experienced decreases in cover were almost always associated with decreases in precipitation. Interestingly, where vegetation cover increased at water‐limited sites, precipitation trends were variable indicating that this is not the only factor driving vegetation response. As Australia is a generally highly water‐limited environment, these findings indicate that the effective availability of water to plants has increased on average over the study period. Results also show that persistent vegetation types have benefited more than recurrent types from recent changes in growing conditions. Regardless of what has been driving these changes, the overall response of vegetation over the past 2–3 decades has resulted in an observable greening of the driest inhabited continent on Earth.

Trends for in situ and Invasive Melanoma in Queensland, Australia, 1982–2002 - Michael Coory; Peter Baade; Joanne Aitken; Mark Smithers; G. Roderick C. McLeod; Ian Ring (Cancer Causes & Control, 2006)

Changes in New Zealand pan evaporation since the 1970s - Michael L. Roderick; Graham D. Farquhar (International Journal of Climatology, 2005)

Gross primary productivity and transpiration flux of the Australian vegetation from 1788 to 1988 AD: effects of CO 2 and land use change - Sandra L. Berry; Michael L. Roderick (Global Change Biology, 2004)
We present a novel approach to estimating the transpiration flux and gross primary productivity (GPP) from Normalized Difference Vegetation Index, leaf functional types, and readily available climate data. We use this approach to explore the impact of variations in the concentration of carbon dioxide in the atmosphere ([CO 2 ]) and consequent predicted changes in vegetation cover, on the transpiration flux and GPP. There was a near 1 : 1 relationship between GPP estimated with this transpiration flux approach and that estimated using a radiation‐use efficiency (RUE) approach. Model estimates are presented for the Australian continent under three vegetation–[CO 2 ] scenarios: the present vegetation and hypothetical ‘natural’ vegetation cover with atmospheric CO 2 concentration ([CO 2 ]) of 350 μmol mol −1 (pveg 350 and nveg 350 ), and for the ‘natural’ vegetation with [CO 2 ] 280 μmol mol −1 (nveg 280 ). Estimated continental GPP is 6.5, 6.3 and 4.3 Gt C yr −1 for pveg 350 , nveg 350 and nveg 280 , respectively . The corresponding transpiration fluxes are 232, 224 and 190 mm H 2 O yr −1 . The contribution of the raingreen and evergreen components of the canopy to these fluxes are also estimated.

Changes in Australian pan evaporation from 1970 to 2002 - Michael L. Roderick; Graham D. Farquhar (International Journal of Climatology, 2004)
Contrary to expectations, measurements of pan evaporation show decreases in many parts of the Northern Hemisphere over the last 50 years. When combined with rainfall measurements, these data show that much of the Northern Hemisphere's terrestrial surface has become less arid over the last 50 years. However, whether the decrease in pan evaporation is a phenomenon limited to the Northern Hemisphere has until now been unknown because there have been no reports from the Southern Hemisphere. Here, we report a decrease in pan evaporation rate over the last 30 years across Australia of the same magnitude as the Northern Hemisphere trends (approximately −4 mm a −2 ). The results show that the terrestrial surface in Australia has, on average, become less arid over the recent past, just like much of the Northern Hemisphere. Copyright © 2004 Royal Meteorological Society.

Soil carbon stocks and bulk density: spatial or cumulative mass coordinates as a basis of expression? - Roger M. Gifford; Michael L. Roderick (Global Change Biology, 2003)
Accounting for CO 2 fluxes by determining changes in stocks of soil carbon (C) as a result of land use change is an option for complying nations under the Kyoto Protocol. The 1996 IPCC guidelines for C accounting recommend that soil C stocks to a depth of 30 cm be used in such accounting. However, the soil bulk density often changes with land use and the soil C per unit ground area to a fixed depth will also change even without any change in the mass fraction of C in dry soil. This problem will generally arise when soil C accounting is taken to a fixed depth (i.e. uses ‘spatial coordinates’). For accuracy in determining the land use change effects on soil C, soil sampling should be referred to a fixed dry soil mass per unit ground area (i.e. use ‘cumulative mass coordinates’). There has been intermittent literature‐discussion about this issue over several decades. Methods to accomplish C accounting on a mass coordinate basis, none of them accurate or efficient, have been suggested. Here, we propose a simple, accurate methodology for determining soil C stocks using cumulative mass coordinates, which does not involve repeat sampling trips, nominal specification of the location of boundaries between soil horizons, or independent sampling for determining soil bulk densities. Each core is taken a little (say 10 cm) below the nominal mass/depth required and the retrieved core is sliced into two at a point a little above the nominal mass/depth (say 10 cm above). An accurate determination of the depth of the core or slice is not needed, but an accurate determination of the dry mass of soil above and below the slice‐point is required. Linear interpolation between these two measurements is then used to estimate the cumulative soil C per unit ground area to the target dry soil mass per unit ground area. Even though this method eliminates the need for reporting soil bulk densities for C accounting, it is urged that the bulk densities and density changes still be routinely reported. This is because such information is of fundamental importance for understanding and predicting the movement of fluids and substances carried in them within the soil and between the soil and the environment. Hence, these data are likely to be of fundamental importance in developing our future understanding and predictive capacity of soil C changes with land use change.

Estimating mixtures of leaf functional types using continental‐scale satellite and climatic data - Sandra L. Berry; Michael L. Roderick (Global Ecology and Biogeography, 2002)
Aim Recent research has shown that much of the variability in leaf gas exchange and leaf longevity can be related to variations in the surface : volume ratio of leaves. The aim of this paper was to develop a theoretical framework and a practical method to extend that result to the vegetation at the continental scale. Location The study was conducted in Australia. Methods We propose that vegetation is composed of a mixture of three basic leaf types, ‘turgor’ (T), ‘mesic’ (M) and ‘sclerophyll’ (S) leaves. Changes in the relative proportions of T, M and S leaves within a vegetation type are visualized using a ternary diagram and differences in vegetation structure are shown to be easily mapped onto the ternary diagram. We estimate the proportions of T, M and S leaves using readily available data. The total amount of PAR absorbed by the vegetation (fPAR) is estimated using continental‐scale satellite observations. The total fPAR is then decomposed into that absorbed by T, M and S leaves. The relative absorption of PAR by T leaves is estimated from the temporal dynamics in the satellite signal, while the relative proportions of M and S leaves are estimated using climatic (solar radiation, rainfall) data. Results When the availability of light, nutrients and water were near‐optimal, the vegetation was composed of predominantly M leaves. In low nutrient environments S leaves predominated. T leaves were dominant in disturbed environments. Conclusions The theoretical framework is used to predict that elevated atmospheric CO 2 would tend to increase the proportion of M and S leaves in an ecosystem and the resulting change means that the proportion of T leaves would decrease. In terms of the TMS scheme, this implies that elevated CO 2 has the same net effect on the vegetation as a decrease in disturbance.

On the direct effect of clouds and atmospheric particles on the productivity and structure of vegetation - Michael L. Roderick; Graham D. Farquhar; Sandra L. Berry; Ian R. Noble (Oecologia, 2001)

Estimating woody and herbaceous vegetation cover from time series satellite observations - Michael L. Roderick; Ian R. Noble; Shane W. Cridland (Global Ecology and Biogeography, 1999)
Summary In this paper we test a method to estimate the tree and grass vegetation cover over Australia from satellite‐derived normalized difference vegetation index (NDVI) time series (monthly 1981–91, ≈5 km pixels) observations. The evergreen cover is assumed to track along the base of the NDVI time series, which is assumed to be equivalent to the woody vegetation cover. The base of the NDVI time series is estimated using modifications to a classical econometric model (i.e. time series is the sum of trend, seasonal and random components). Estimates of the average evergreen component during 1982–85 and 1986–89 were generally consistent with known vegetation distributions. Changes in evergreen cover were largely restricted to the south‐west and south‐east of Australia. Those changes were largely the result of differences in rainfall between the two periods. The proposed method for estimating woody vegetation cover is found to be generally robust. However, there are some regions where the grass (or pasture) is mostly evergreen. Some possible refinements are proposed to handle such cases.